Efektivitas Video Edukasi Irigasi Hidung Terhadap Kesembuhan Pasien Rhinorrhea di RSUD Ibnu Sina Gresik - Fitriah, Hana Azizatul; Hutahaean, Fransiska; Milyantono, Riyan Charlie (Jurnal Kesehatan Andalas, 2024)
Rhinorrhea is a predominant symptom of nasal inflammation that comes from the nose's activation glands to produce mucus. Objective: To found out the effectiveness of providing nasal irrigation educational videos on the recovery rate of rhinorrhea patients at the Ibnu Sina Gresik Hospital. Methods: This research used a quasi-experimental design was applied by employing Jamovi to do univariate analysis in describing the characteristics of each variable, such as age, gender, level of education, and Rhinorrhea as the predominant disease. In addition, bivariate analysis used chi-square to test the effectiveness differentiation of giving nasal irrigation video to patients who received the video and patients who did not. Results: Univariate analysis reported that 21 patients were male (52,5%), 12 patients (47,5%) were between 20-44 years old, 16 patients (40%) experienced high school level, and 11 patients (27,5%) had vasomotor rhinitis disease. Chi-square analysis showed a significance value of 0.685, indicating no difference in the recovery rate between rhinorrhea patients receiving nasal irrigation video and those not receiving it. Conclusion: There is no significant difference in the recovery of rhinorrhea outpatients who received and those who did not receive educational videos about nasal irrigation.Keywords: educational video, rhinorrhea, recovery rate